Dinohippus mexicanus (Early-Late, Late, and Latest Hemphillian) and the Transition to Genus Equus, in Central Mexico Faunas - Carranza-Castañeda, Oscar (Frontiers in Earth Science, 2019)
In the advances of the research of the sedimentary basins from central Mexico, it is significant the discovery of the first records of equids of Clarendonian and early Hemphillian age that are mentioned. The specimens were collected in southwest deposits of the San Miguel de Allende basin, the ages are verified by radiometric dates The largest collection of Dinohippus mexicanus skulls jaws and isolated teeth recovered, have shown the wide geographical distribution in faunas of central Mexico. The study of these records from localities of Coecillos, Rinconada, Arroyo Emilio and Rancho el Ocote faunas of the San Miguel Allende, Guanajuato state, Tecolotlán, Jalisco state and Juchipila basin Zacatecas state, have shown the variability and transitional features they have in the structures of the skull and upper and lower molars. The skull from Tecolotlán and Rancho El Ocote, of the late Hemphillian age present a well-defined dorsal fossa, in contrast the oldest skull from early-late Hemphillian of Juchipila, the fossa is just a depression in the Maxillary and nasal bone, however, the skull from Coecillos has structures that differentiate it from others. The most relevant records are the lower and upper molars collected at the top of the biostratigraphic sequence of Rancho El Ocote, in the sites named GTO 2 site D and F. These specimens present features that differentiate them from Dinohippus and suggest a primitive Equus. Upper teeth from the Blancan age of Tecolotlán basin, have a high crown but a pronounced curvature like the Dinohippus mexicanus collected in the late Hemphillian strata of this basin.